Extensive Host Sharing of Central European Tula Virus - Schmidt-Chanasit, Jonas (American Society for Microbiology (ASM), 2010)
To examine the host association of Tula virus (TULV), a hantavirus present in large parts of Europe, we investigated a total of 791 rodents representing 469 Microtus arvalis and 322 Microtus agrestis animals from northeast, northwest, and southeast Germany, including geographical regions with sympatric occurrence of both vole species, for the presence of TULV infections. Based on serological investigation, reverse transcriptase PCR, and subsequent sequence analysis of partial small (S) and medium (M) segments, we herein show that TULV is carried not only by its commonly known host M. arvalis but also frequently by M. agrestis in different regions of Germany for a prolonged time period. At one trapping site, TULV was exclusively detected in M. agrestis, suggesting an isolated transmission cycle in this rodent reservoir separate from spillover infections of TULV-carrying M. arvalis. Phylogenetic analysis of the S and M segment sequences demonstrated geographical clustering of the TULV sequences irrespective of the host, M. arvalis or M. agrestis. The novel TULV lineages from northeast, northwest, and southeast Germany described here are clearly separated from each other and from other German, European, or Asian lineages, suggesting their stable geographical localization and fast sequence evolution. In conclusion, these results demonstrate that TULV represents a promiscuous hantavirus with a large panel of susceptible hosts. In addition, this may suggest an alternative evolution mode, other than a strict coevolution, for this virus in its Microtus hosts, which should be proven in further large-scale investigations on sympatric Microtus hosts.